Viability Test Device for anisakid nematodes. Issue 3 (March 2018) - Kroeger, Michael; Karl, Horst; Simmler, Bernhard; Singer, Peter
Abstract: Up to now the visual inspection of mobility of isolated anisakid larvae serves as a measure of viability and possible risk of infection. This paper presents a new method to rule out unreliability – caused by the temporary immobility of the larvae and by the human uncertainty factor of visual observation. By means of a Near infrared (NIR) imaging method, elastic curvature energies and geometric shape parameters were determined from contours, and used as a measure of viability. It was based on the modelling of larvae as a cylindrical membrane system. The interaction between curvatures, contraction of the longitudinal muscles, and inner pressure enabled the derivation of viability from stationary form data. From series of spectrally signed images within a narrow wavelength range, curvature data of the larvae were determined. Possible mobility of larvae was taken into account in statistical error variables. Experiments on individual living larvae, long-term observations of Anisakis larvae, and comparative studies of the staining method and the VTD measurements of larvae from the tissue of products confirmed the effectiveness of this method. The VTD differentiated clearly between live and dead nematode larvae isolated from marinated, deep-frozen and salted products. The VTD has been proven as excellent method to detect living anisakid nematode larvae in fishery products and is seen as useful tool for fish processing industry and control authorities.